Решить выражения с решением -(2x-3y)+(6x-3y)+28x; 5(3x+2y)-7(2x-6y)-52y; 7(5x-6y)-3(8x-7y)+21y; 6(5x--50y)+4y; -8(7x-6y)+(67x-48y); 8(7x-6y)-5(4x-3y)+33y

egorpolozuk egorpolozuk    3   14.07.2019 18:20    0

Ответы
9petya 9petya  20.09.2020 17:20
1)-(2x-3y)+(6x-3y)+28x=-2x+3y+6x-3y+28x=32x
2)5(3x+2y)-7(2x-6y)-52y=15x+10y-14x+42y-52y=x
3)7(5x-6y)-3(8x-7y)+21y=35x-42y-24x+21y+21y=11x
4)6(5x-9y)-(29x-50y)+4y=30x-54y-29x+50y+4y=x
5)-8(7x-6y)+(67x-48y)=-56x+48y+67x-48y=11x
6)8(7x-6y)-5(4x-3y)+33y=56x-48y-20x+15y+33y=36x
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика